Intranasal insulin prevents anesthesia-induced hyperphosphorylation of tau in 3xTg-AD mice - Chen, Yanxing; Run, Xiaoqin; Liang, Zhihou; Zhao, Yang; Dai, Chun-ling; Iqbal, Khalid; Liu, Fei; Gong, Cheng-Xin (Frontiers in Aging Neuroscience, 2014)
Background: It is well documented that elderly individuals are at increased risk of cognitive decline after anesthesia. General anesthesia is believed to be a risk factor for Alzheimer’s disease (AD). Recent studies suggest that anesthesia may increase the risk for cognitive decline and AD through promoting abnormal hyperphosphorylation of tau, which is crucial to neurodegeneration seen in AD. Methods: We treated 3xTg-AD mice, a commonly used transgenic mouse model of AD, with daily intranasal administration of insulin (1.75U/day) for one week. The insulin- and control-treated mice were then anesthetized with single intraperitoneal injection of propofol (250 mg/kg body weight). Tau phosphorylation and tau protein kinases and phosphatases in the brains of mice 30 min and two hours after propofol injection were then investigated by using Western blots and immunohistochemistry. Results: Propofol strongly promoted hyperphosphorylation of tau at several AD-related phosphorylation sites. Intranasal administration of insulin attenuated propofol-induced hyperphosphorylation of tau, promoted brain insulin signaling, and led to up-regulation of protein phosphatase 2A, a major tau phosphatase in the brain. Intranasal insulin also resulted in down-regulation of several tau protein kinases, including cyclin-dependent protein kinase 5, calcium/calmodulin-dependent protein kinase II, and c-Jun N-terminal kinase. Conclusion: Our results demonstrate that pretreatment with intranasal insulin prevents AD-like tau hyperphosphorylation. These findings provide the first evidence supporting that intranasal insulin administration might be used for the prevention of anesthesia-induced cognitive decline and increased risk for AD and dementia.